Edukasi Limbah B3 Hasil Rumah Tangga Sebagai Langkah Awal Untuk Pelestarian Lingkungan - Wahyu Maulana Endris; Muhammad Rayhan; Ramdhan Yurianto (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Hazardous and toxic waste management poses a global challenge that requires serious attention in environmental conservation efforts. This article discusses the introduction of hazardous waste to the community as a first step in reducing environmental impacts. Taking the example of Banyumas, Central Java, which is one of the largest waste processing areas in Southeast Asia, this article highlights the success of hazardous waste management in supporting conservation efforts. Based on various sources of literature, including research on waste management education, innovative waste management practices, and hazardous waste introduction programs in various countries, this article concludes that educating the public about hazardous waste is a crucial step in creating a cleaner and more sustainable environment. Recommendations for community service programs are also provided, including diversifying educational materials, strengthening cooperation with relevant stakeholders, and ongoing evaluation to improve program effectiveness. It is hoped that through continuous and targeted efforts, communities can become more aware of the importance of hazardous waste management and actively contribute to environmental conservation for future generations.